Yam improvement for income and food security in west Africa: effectiveness of a multidisciplinary and multiinstitutional teamwork - Maroya, N.; Asiedu, Robert; Mignouna, Djana B.; López Montes, Antonio José; Kleih, Uli K.; Phillips, D.; Ndiame, F.; Ikeorgu, J.; Otoo, E. (2015)
The overall goal of the five year project “Yam Improvement for Income and Food Security in West Africa” (YIIFSWA) funded by the Bill and Melinda Gates Foundation and led by the International Institute of Tropical Agriculture, Ibadan, Nigeria was to: (a) increase yam productivity by 40% for 2,00,000 smallholder yam farmers in Ghana and Nigeria and (b) deliver key global good research products that will contribute to the 10-year overall vision to sustainably double incomes from yams for 3 million smallholder yam farming families and contribute to ensuring food security for producers and consumers. Implemented by scientists of twenty partner specialized organizations, comprising research institutes, Universities, governmental and non-governmental organizations, YIIFSWA has impacted yam value chain stakeholders through research and development interventions. The significant contributions made in the project during the past 18 months’ period are discussed in this paper. These include: a baseline survey conducted in key yam growing areas in Ghana and Nigeria, training of yam producers on adapted yam minisett technique and production of seed yam, undertaking in depth value chain assessments, developing the capacity of Farmers Organizations (FOs) by linking them to service providers (SPs), participatory evaluation of new yam genotypes, successful development of yam virus diseases diagnostics and development of novel techniques for high ratio yam propagation such as aeroponics and bioreactors.The overall goal of the five year project “Yam Improvement for Income and Food Security in West Africa” (YIIFSWA) funded by the Bill and Melinda Gates Foundation and led by the International Institute of Tropical Agriculture, Ibadan, Nigeria was to: (a) increase yam productivity by 40% for 2,00,000 smallholder yam farmers in Ghana and Nigeria and (b) deliver key global good research products that will contribute to the 10-year overall vision to sustainably double incomes from yams for 3 million smallholder yam farming families and contribute to ensuring food security for producers and consumers. Implemented by scientists of twenty partner specialized organizations, comprising research institutes, Universities, governmental and non-governmental organizations, YIIFSWA has impacted yam value chain stakeholders through research and development interventions. The significant contributions made in the project during the past 18 months’ period are discussed in this paper. These include: a baseline survey conducted in key yam growing areas in Ghana and Nigeria, training of yam producers on adapted yam minisett technique and production of seed yam, undertaking in depth value chain assessments, developing the capacity of Farmers Organizations (FOs) by linking them to service providers (SPs), participatory evaluation of new yam genotypes, successful development of yam virus diseases diagnostics and development of novel techniques for high ratio yam propagation such as aeroponics and bioreactors.The overall goal of the five year project “Yam Improvement for Income and Food Security in West Africa” (YIIFSWA) funded by the Bill and Melinda Gates Foundation and led by the International Institute of Tropical Agriculture, Ibadan, Nigeria was to: (a) increase yam productivity by 40% for 2,00,000 smallholder yam farmers in Ghana and Nigeria and (b) deliver key global good research products that will contribute to the 10-year overall vision to sustainably double incomes from yams for 3 million smallholder yam farming families and contribute to ensuring food security for producers and consumers. Implemented by scientists of twenty partner specialized organizations, comprising research institutes, Universities, governmental and non-governmental organizations, YIIFSWA has impacted yam value chain stakeholders through research and development interventions. The significant contributions made in the project during the past 18 months’ period are discussed in this paper. These include: a baseline survey conducted in key yam growing areas in Ghana and Nigeria, training of yam producers on adapted yam minisett technique and production of seed yam, undertaking in depth value chain assessments, developing the capacity of Farmers Organizations (FOs) by linking them to service providers (SPs), participatory evaluation of new yam genotypes, successful development of yam virus diseases diagnostics and development of novel techniques for high ratio yam propagation such as aeroponics and bioreactors.The overall goal of the five year project “Yam Improvement for Income and Food Security in West Africa” (YIIFSWA) funded by the Bill and Melinda Gates Foundation and led by the International Institute of Tropical Agriculture, Ibadan, Nigeria was to: (a) increase yam productivity by 40% for 2,00,000 smallholder yam farmers in Ghana and Nigeria and (b) deliver key global good research products that will contribute to the 10-year overall vision to sustainably double incomes from yams for 3 million smallholder yam farming families and contribute to ensuring food security for producers and consumers. Implemented by scientists of twenty partner specialized organizations, comprising research institutes, Universities, governmental and non-governmental organizations, YIIFSWA has impacted yam value chain stakeholders through research and development interventions. The significant contributions made in the project during the past 18 months’ period are discussed in this paper. These include: a baseline survey conducted in key yam growing areas in Ghana and Nigeria, training of yam producers on adapted yam minisett technique and production of seed yam, undertaking in depth value chain assessments, developing the capacity of Farmers Organizations (FOs) by linking them to service providers (SPs), participatory evaluation of new yam genotypes, successful development of yam virus diseases diagnostics and development of novel techniques for high ratio yam propagation such as aeroponics and bioreactors.The overall goal of the five year project “Yam Improvement for Income and Food Security in West Africa” (YIIFSWA) funded by the Bill and Melinda Gates Foundation and led by the International Institute of Tropical Agriculture, Ibadan, Nigeria was to: (a) increase yam productivity by 40% for 2,00,000 smallholder yam farmers in Ghana and Nigeria and (b) deliver key global good research products that will contribute to the 10-year overall vision to sustainably double incomes from yams for 3 million smallholder yam farming families and contribute to ensuring food security for producers and consumers. Implemented by scientists of twenty partner specialized organizations, comprising research institutes, Universities, governmental and non-governmental organizations, YIIFSWA has impacted yam value chain stakeholders through research and development interventions. The significant contributions made in the project during the past 18 months’ period are discussed in this paper. These include: a baseline survey conducted in key yam growing areas in Ghana and Nigeria, training of yam producers on adapted yam minisett technique and production of seed yam, undertaking in depth value chain assessments, developing the capacity of Farmers Organizations (FOs) by linking them to service providers (SPs), participatory evaluation of new yam genotypes, successful development of yam virus diseases diagnostics and development of novel techniques for high ratio yam propagation such as aeroponics and bioreactors.The overall goal of the five year project “Yam Improvement for Income and Food Security in West Africa” (YIIFSWA) funded by the Bill and Melinda Gates Foundation and led by the International Institute of Tropical Agriculture, Ibadan, Nigeria was to: (a) increase yam productivity by 40% for 2,00,000 smallholder yam farmers in Ghana and Nigeria and (b) deliver key global good research products that will contribute to the 10-year overall vision to sustainably double incomes from yams for 3 million smallholder yam farming families and contribute to ensuring food security for producers and consumers. Implemented by scientists of twenty partner specialized organizations, comprising research institutes, Universities, governmental and non-governmental organizations, YIIFSWA has impacted yam value chain stakeholders through research and development interventions. The significant contributions made in the project during the past 18 months’ period are discussed in this paper. These include: a baseline survey conducted in key yam growing areas in Ghana and Nigeria, training of yam producers on adapted yam minisett technique and production of seed yam, undertaking in depth value chain assessments, developing the capacity of Farmers Organizations (FOs) by linking them to service providers (SPs), participatory evaluation of new yam genotypes, successful development of yam virus diseases diagnostics and development of novel techniques for high ratio yam propagation such as aeroponics and bioreactors.The overall goal of the five year project “Yam Improvement for Income and Food Security in West Africa” (YIIFSWA) funded by the Bill and Melinda Gates Foundation and led by the International Institute of Tropical Agriculture, Ibadan, Nigeria was to: (a) increase yam productivity by 40% for 2,00,000 smallholder yam farmers in Ghana and Nigeria and (b) deliver key global good research products that will contribute to the 10-year overall vision to sustainably double incomes from yams for 3 million smallholder yam farming families and contribute to ensuring food security for producers and consumers. Implemented by scientists of twenty partner specialized organizations, comprising research institutes, Universities, governmental and non-governmental organizations, YIIFSWA has impacted yam value chain stakeholders through research and development interventions. The significant contributions made in the project during the past 18 months’ period are discussed in this paper. These include: a baseline survey conducted in key yam growing areas in Ghana and Nigeria, training of yam producers on adapted yam minisett technique and production of seed yam, undertaking in depth value chain assessments, developing the capacity of Farmers Organizations (FOs) by linking them to service providers (SPs), participatory evaluation of new yam genotypes, successful development of yam virus diseases diagnostics and development of novel techniques for high ratio yam propagation such as aeroponics and bioreactors.